Propuesta pedagógica en torno a tópicos introductorios de física nuclear - Ramos G., E. P.; Peralta M., J. J.; Monroy C., I. A.; Cardona R., G. (Revista Científica, 2011)
Teaching physics research in school environment has shown a great tendency in different countries to propose new objectives inside it, among which are also, the recognition and description of introductory concepts about modern physics in high school, in our particular interest, teaching of nuclear physics. On the other hand, the methods used in teaching of some of those topics do not suppose an efficient methodology, raising the need of a new focus to approach this type of topics to optimize their learning in school. We propose different activities from cooperative-colaborative learning methodology, with the objective to approach the teaching of introductory topics of nuclear physics (atomic structure and nuclear fusion); where these are teach from different experiences in the classroom that simulate the phenomena that are related to the different themes. Adjunct to the activities we included animations that support the material used in class.